2015
DOI: 10.1176/appi.ajp.2015.15040465
|View full text |Cite
|
Sign up to set email alerts
|

Ketamine and Other NMDA Antagonists: Early Clinical Trials and Possible Mechanisms in Depression

Abstract: The antidepressant efficacy of ketamine, and perhaps D-cycloserine and rapastinel, holds promise for future glutamate-modulating strategies; however, the ineffectiveness of other NMDA antagonists suggests that any forthcoming advances will depend on improving our understanding of ketamine's mechanism of action. The fleeting nature of ketamine's therapeutic benefit, coupled with its potential for abuse and neurotoxicity, suggest that its use in the clinical setting warrants caution.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
377
2
4

Year Published

2016
2016
2020
2020

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 501 publications
(413 citation statements)
references
References 172 publications
8
377
2
4
Order By: Relevance
“…In addition, most current antidepressants can take weeks before patients or animal models feel the full antidepressant effects (42,43). Recently, we reported that a single dose of N-methyl-D-aspartate (NMDA) receptor antagonist ketamine (or R-ketamine) showed a rapid antidepressant effect in the social defeat stress model (37,39), consistent with rapid antidepressant effects of ketamine in treatmentresistant patients with depression (44)(45)(46). However, ketamine leads to psychotomimetic side effects and abuse liability that appears to be absent in the case of TPPU.…”
Section: Discussionmentioning
confidence: 71%
“…In addition, most current antidepressants can take weeks before patients or animal models feel the full antidepressant effects (42,43). Recently, we reported that a single dose of N-methyl-D-aspartate (NMDA) receptor antagonist ketamine (or R-ketamine) showed a rapid antidepressant effect in the social defeat stress model (37,39), consistent with rapid antidepressant effects of ketamine in treatmentresistant patients with depression (44)(45)(46). However, ketamine leads to psychotomimetic side effects and abuse liability that appears to be absent in the case of TPPU.…”
Section: Discussionmentioning
confidence: 71%
“…123,124 Along with its rapid behavioral effects, ketamine increases synaptogenesis in rodents through rapid release of BDNF in an activity-dependent manner. 104,125 Furthermore, recent evidence suggests that the therapeutic effects of ketamine may be mediated through epigenetic mechanisms.…”
Section: Antidepressants Alter Cellular Functioning Through Epigenementioning
confidence: 99%
“…The antidepressant effect of sub-anesthetic doses of ketamine has been demonstrated in several studies in mice (Maeng et al 2008, Popik et al 2008, Silva et al 2010, rats (Akinfiresoye and Tizabi 2013, Fraga et al 2013, Garcia et al 2008a, b, 2009, Li et al 2010, Parise et al 2013, Popik et al 2008, Reus et al 2011, Tizabi et al 2012, Yang et al 2012) and humans (Maeng and Zarate 2007, Rot et al 2010, Zarate et al 2006, and the investigation of its mechanism of action or even the involvement of active metabolites is an active field of research (Li et al 2010, Newport et al 2015, Zanos et al 2016). Contrary to our results, there are few works successfully describing the use of ketamine repeated treatment to mimic schizophrenia negative symptoms in the forced swimming.…”
Section: Discussionmentioning
confidence: 99%